Consumer Protection in Digital Transactions: An Analysis of Regulatory Effectiveness from Legal and Economic Perspectives - Ermini; Ramanata Disurya; Layang Sardana; Sri Husnulwati; Suryati (Indonesian Journal Publisher, 2026)
This study aims to analyze the effectiveness of consumer protection regulations in digital transactions in Indonesia from both legal and economic perspectives. Using a qualitative descriptive method through a library research approach, the study explores relevant laws, government regulations, academic publications, and institutional reports. Data were collected through literature review and document analysis, followed by thematic and inductive interpretation to identify patterns related to legal enforcement, regulatory gaps, and market efficiency. The findings indicate that while Indonesia’s regulatory framework—comprising Law No. 8 of 1999 on Consumer Protection, Law No. 11 of 2008 on Electronic Information and Transactions, Government Regulation No. 80 of 2019 on Electronic Trade, and Law No. 27 of 2022 on Personal Data Protection—is normatively comprehensive, its implementation remains weak. The study reveals persistent issues such as overlapping institutional authority, limited enforcement capacity, low consumer literacy, and minimal compliance incentives for digital business actors. From an economic standpoint, these weaknesses contribute to high transaction costs, information asymmetry, and inefficiency in e-commerce markets. The research underscores the need for adaptive, harmonized, and incentive-based regulatory mechanisms to foster a safer and more transparent digital marketplace. It concludes that strengthening inter-agency coordination, enhancing consumer awareness, and promoting digital ethics are crucial to achieving sustainable consumer protection in Indonesia’s growing digital economy.